ANY P-WAVE KINEMATIC ALGORITHM FOR VERTICAL TRANSVERSELY ISOTROPIC MEDIA CAN BE ADAPTED TO MODERATELY ANISOTROPIC MEDIA OF ARBITRARY SYMMETRY TYPE - Rasolofosaon P.N.J. (My University, 2003)
Most of P-wave anisotropic kinematic algorithms (modeling, processing, and inversion) have been developed for the case of Transverse Isotropy (TI). Does it mean that when dealing with more complex symmetry types (Arbitrarily tilted TI, orthorhombic, monoclinic or even triclinic), all these algorithms are irrelevant? In fact, not at all. It has recently been demonstrated that in 2D geometry any qP-wave TI kinematic algorithm can be simply generalized to the case of monoclinic symmetry using the so-called Azimuthally Dependent Anisotropy Parameter Transformation (ADAPT), assuming moderate anisotropy. The extension of the technique to the case of arbitrary anisotropy type (triclinic) is achieved in this paper. The method is successfully checked for seismic modeling in a full 2D model with layers of contrasted anisotropy types and with arbitrary vertical and horizontal velocity variations (non-constant gradient). Typically, the approximate travel times using ADAPT differ from the exact travel times by a few milliseconds for total travel times of the order of a few seconds. Applications to seismic processing are also described. The simplicity of the procedure and the generality of the applicability of the ADAPT recipe are striking and very convenient for practical applications. They certainly deserve further analysis.
Keywords: P-WAVE KINEMATICS; ARBITRARY ANISOTROPY; SEISMIC ANISOTROPY